The Influence of Business Models, Information Technology on the Quality of Accounting Information Systems Digitizing MSMEs Post-COVID-19 - S Supriyati; Sri Mulyani; Harry Suharman; Taufiq Supriadi (Faculty of Computer Science Universitas Indonesia, 2022)
Many organizations realize the importance of building information systems based on the formulation of business models and implementing them into company activities. The survival of an organization is determined by its ability to compete in the market. In modern systems, there are dependencies between enterprise information systems, business models and enterprise business processes. There is an equally strong influence between business models and information systems. The goal achieved between business models and information systems is to maintain a balance between the three dimensions of sustainable development, namely: environmental, social, and economic. The research method used is qualitative with a field approach, an institutional approach, and a library approach. The types of data used in this research are primary data and secondary data. The data collection technique used is observation and literature study both nationally and internationally, while secondary data comes from journals, proceedings, government regulations, and statutory regulations. The output target achieved is obtaining business models, information technology on the quality of MSME accounting information systems after Covid-19.